Endovascular Treatment of Middle Cerebral Artery Aneurysms with Flow Modification with the Use of the Pipeline Embolization Device - Yavuz, K.; Geyik, S.; Saatci, I.; Cekirge, H.S. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: The Pipeline Embolization Device was reported to be safe and effective in the treatment of sidewall aneurysms, preserving the patency of the vessels covered by the construct. However, to date, the safety and efficacy of this device in treating bifurcation aneurysms remains unknown. We report our preliminary experience with the use of the Pipeline Embolization Device in the management of MCA aneurysms located at the bifurcations, including mid- and long-term follow-up data. MATERIALS AND METHODS: Wide-neck MCA aneurysms, which give rise to a bifurcating or distal branch in which other endovascular techniques are thought to be unfeasible or more risky, were included. Data including demographics, aneurysm features, antiplatelet therapy, complications, and angiographic follow-up results for up to 30 months were recorded. RESULTS: Twenty-five aneurysms located at the MCA bifurcation (n = 21) or distal (n = 4) were treated. Of these, 22 were small and 3 were large. A single device was used in all but 2. No deaths occurred in the series. All patients had at least 1 control angiographic study, 21 of which were DSA (3–30 months), which showed that 12 of the rising branches were patent whereas 6 were filling in reduced caliber and 3 were occluded asymptomatically. According to the last angiographic follow-up, complete occlusion was revealed in 21 of 25 aneurysms (84%). CONCLUSIONS: The Pipeline Embolization Device provides a safe and effective treatment alternative for wide-neck MCA aneurysms that give rise to a bifurcating or distal branch when other endovascular techniques are thought to be unfeasible or more risky. PEDPipeline Embolization Device